Revascularization versus medical therapy in patients aged 80 and older with stable ischemic heart disease. Issue 12 (7th August 2021) - Phan, Derek Q.; Zadegan, Ray; Lee, Ming‐Sum
Abstract: Background: Older patients are underrepresented in landmark randomized trials for stable ischemic heart disease (SIHD). Therefore, we sought to evaluate the benefits of revascularization in patients ≥80 years old with SIHD. Methods: Retrospective study of patients undergoing invasive coronary angiography (ICA) for SIHD between 2009 and 2019. Patients were grouped according to treatment: revascularization (percutaneous coronary intervention [PCI] or coronary artery bypass grafting [CABG]) versus initial medical therapy alone. Inverse probability of treatment weighting (IPTW)‐adjusted Cox proportional hazard regression analyses were performed. Outcomes evaluated were all‐cause mortality, non‐fatal myocardial infarction (MI), and repeat revascularization. Results: A total of 1015 patients (median age 83.0, interquartile range [IQR] 81.3–85.2 years; 29% female) underwent ICA for SIHD. Of these, 557 (55%) were treated with revascularization and 458 (45%) with initial medical therapy alone. Baseline characteristics were well balanced after IPTW adjustment. At median follow‐up of 3.5 years (IQR 1.7–5.9 years), there were no differences in all‐cause mortality and non‐fatal MI between treatment groups; but there was an increased need for repeat revascularization (IPTW adjusted hazard ratio 2.22, 95% confidence interval 1.53–3.22) with revascularization. Separately comparing PCI or CABG alone versus medical therapy yielded similar results; as well as in subgroup analysis (except for patients ≥90 years old and those without prior CABG). Conclusion: There were no differences in all‐cause mortality and non‐fatal MI with invasive revascularization (either PCI or CABG) versus medical therapy alone in patients ≥80 years old with SIHD. Large randomized trials focusing on older patients are warranted to guide clinical practice in this growing population.